Marginalizing colonial violence at the beginning of the 21st century The representation of colonial military expedition to Banten of 1808 in the National Museum of Indonesia - Fajri, Adieyatna (Wacana, Journal of the Humanities of Indonesia, 2023)
The article discusses the narrative of colonial violence attached to the objects displayed in the National Museum of Indonesia in Jakarta. Taking the colonial military expedition to Banten in 1808 as a case study, this paper analyses the exhibition to show the interplay between museum as a product of colonialism and its focus on regionalism, its role in post-colonial nation-state-formation promoting national identity building, and the complexities of addressing violence. It argues that, as the museum engages with the discourse of coloniality and concurrently emphasizes national identity building, it inadvertently marginalizes the narrative of colonial violence. The findings show that, despite the abundant references to events and processes of direct and structural violence, the phenomenon of violence as an instrumental practice of colonialism has never been discussed or made the object of explicit analysis in the museum. Instead, the museum promotes a belief in a benign and benevolent Dutch imperialism.